Speak Out Your Films: When Asian Independent Film Festivals Send Messages to the World - Zaki Habibi (Program Studi Ilmu Komunikasi, 2012)
This article focuses on three independent film festivals held in three different countries in Asia. They are (1) Jeonju International Film Festival (JIFF) in Jeonju, South Korea, (2) Cinemalaya Philippine Independent Film Festival in Manila, The Philippines, and (3) Jogja-NETPAC Asian Film Festival (JAFF) in Yogyakarta, Indonesia. Multiple case studies is adopted to analyze the way in which these three independent film festivals are being organized, including the “messages” being circulated for their global audiences. The findings are analyzed based on the conceptual framework that consists of three relevant concepts: film as cultural product, independent film festival, and cultural discourse. The conclusion shows that the three analyzed film festivals offer an alternative way in film distribution, then demonstrate unconventional way of festival organizing, and strengthening the power of community and its networks as the basis for the development of their festivals.